The Influence of China's Economic Reforms (1978-2020) on the Growth of Fintech in China - Abbas, Syed Tahir; Li, Li (PT FORMOSA CENDEKIA GLOBAL, 2024)
This paper examines the influence of China's economic reforms from 1978 to 2020 on the growth and development of fintech in the country. Initiated under Deng Xiaoping, these reforms transitioned China from a centrally planned economy to a market-oriented one, fostering unprecedented economic growth and modernization. This study explores how key reforms, such as the decentralization of economic decision-making, the establishment of Special Economic Zones (SEZs), and the opening up to foreign investment, have impacted the fintech sector. By analyzing early developments, key players, and technological advancements in fintech, the paper highlights the pivotal role of economic policies and investments in shaping China's digital financial landscape. The research employs qualitative methods, including interviews with industry experts and analysis of relevant documents, to provide a comprehensive understanding of the sector's evolution. The findings reveal that China's economic reforms have significantly influenced fintech growth, offering valuable insights for policymakers, businesses, and researchers interested in the interplay between economic policy and technological innovation.